Analisis Dampak Pengembangan Desa Wisata Adventure Tourism Village Terhadap Ekonomi, Sosial dan Pendidikan Masyarakat - Muhamad Sarifudin; Sudati Nur Sarfiah; Gentur Jalunggono (Universitas Tidar, 2019)
Tourism development and development is an effort to develop and utilize tourist attractions, such as culture, nature and ancient relics by involving the community so that they can have a positive impact on people's welfare. With the development of the tourist village of Candirejo the village government empowers some people to contribute to tourism activities. This study aims to determine the impact of the development of Candirejo tourism village on the economic, social and educational communities that contribute to tourism activities. This study uses descriptive data analysis techniques using the Likers scale supported by interviews and documentation. While the method of writing data uses qualitative descriptive methods. Calculation of the average (mean) data from each yielding variable in the tourism village development variable has an average of 4.41, economic 4.11, social 3.98, and education 4,22. From the results of the calculation above shows that the community of tourism actors agree with the development of the tourism village of Candirejo which has an impact on the economic, social, and education of the people who contribute as tourism actors.